GAMBARAN GEJALA PSIKOSOMATIS PADA SANTRI TAHFIDZ DI PESANTREN NIZAMUDDIN PALOPO - Athiyyah, Ayumi; Suarja, Septya; Kadir, Abdul; Fahmi, Ainul (IKIP Siliwangi, 2025)
This study aims to describe the psychosomatic symptoms experienced by tahfidz students at Pesantren Nizamuddin Palopo and analyze the factors and implications for the learning process in pesantren education. Tahfidz students face high cognitive and emotional loads in the process of memorizing the Qur'an, which can trigger psychosomatic symptoms such as migraines, sleep disorders and other physical complaints without clear medical causes. This study used a qualitative research method with a phenomenological approach. The informants in the study were 5 female students of tahfidz Nizamuddin Palopo. Data collection techniques through observation, interviews and documentation. The results showed that there were tahfidz students who experienced psychosomatic symptoms related to the pressure of memorizing the Al-Qu'an, stress and anxiety as well as negative feelings and thoughts. The psychosomatic symptoms experienced by tahfidz students are symptoms in the head and gastrointestinal parts, symptoms of fatigue and sleep disturbances and symptoms in the chest and frequency changes. The novelty of this research is that it focuses on tahfidz students, which is a group involved in memorizing the Al-Qur'an. The findings show the importance of integrating a psychopedagogical approach in the tahfidz curriculum and coaching students, in order to create a healthy and sustainable learning environment. This research contributes to the development of a more holistic education, by considering mental health aspects as an integral part of the Islamic education process.